PEMANFAATAN PODCAST DAN KOVERGENSI MEDIA INFORMASI PERUSAHAAN SEBAGAI MEDIA PUBLIC RELATIONS - Fitriah, Dina; Mukhlisiana, Lusy (Linimasa : Jurnal Ilmu Komunikasi, 2024)
ABSTRACT Communication technology transformation has been widely used by companies to disseminate information to internal and external parties of the company. Like the use of podcasts as a medium used by companies to build information media. Changes in technology into new media practices are the impact of media convergence. The object of this research is the Witel Cirebon Podcast (POWER). The purpose of this study is to examine the utilization of the Witel Cirebon Podcast (POWER) as a form of transformation of old media into new media which is used to disseminate communication and information about Telkom Indonesia Witel Cirebon, and to find out the planning and management of the Witel Cirebon Podcast as a company information medium. This study uses a qualitative descriptive method. The results of this study indicate that in utilizing the Witel Cirebon Podcast (POWER), there is a team that manages the Podcast, namely the social media ranger team to carry out the planning and management of the content of the Witel Cirebon Podcast to build the company's image, reputation and promotional activities through the development of digital information and communication media.   Keywords: Media Convergence, Podcast, Public Relations